Burrowing Time of the Three Indonesian Hippoid Crabs After Artificial Dislodgment - Yusli Wardiatno; Yuyun Qonita; Agus Alim Hakim (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Three species of hippoid crabs are the target species of intertidal fishery along coastal line in District Cilacap, south Java; namely Emerita emeritus, Hippa adactyla and Albunea symmista. In Adipala sandy beach, Cilacap  an experiment was conducted to reveal the burrowing time and velocity of the crabs. The experiment was performed by removing the crabs from their burrows, measuring their carapace length, and releasing them immediately on the substrate. Burrowing time was measured from the start of burrowing to the disappearance of the entire carapace under the sediment surface. Among the three species, E. emeritus had the fastest burrowing time. As a consequence in terms of velocity, the burrowing velocity of Albunea symmista was higher than that of Hippa adactyla and Emerita emeritus; meaning that with the same size A. symmista needs longer time to burrow. By evaluating with other previous studies, the burrowing time and burrowing velocity of the three sand crabs were comparable. The ability of fast burrowing in the three species seems likely to be the advantage for their survival in large wave disturbed coarse sandy habitat and for their ability to widely exist along the sandy coast of south Java. Keywords: behavior; Indian ocean; intertidal; sand crab; south Java; swash zone